Effectiveness of a Specific and Time-Efficient Warm-Up Protocol on Strength Performance among Trained Soccer Players - Madarsa, Nor Ikhmar; Mohamad Shalan, Nor Aijratul Asikin; Md Nadzalan, Ali; Mohamad, Nur Ikhwan (Jurnal Pendidikan Bitara UPSI, 2024)
Resistance training is crucial for soccer players as it enhances their overall physical performance, contributing significantly to strength, power, and injury prevention. A well-structured warm-up enhances physiological readiness, reduces the risk of injury, and optimizes performance during resistance training sessions. The debate between general and specific warm-ups is ongoing, with various studies highlighting the advantages and disadvantages of each approach. Hence, this study investigated the effectiveness of specific and time-efficient warm-up protocols on strength performance, mainly focusing on the one-repetition maximum (1RM) barbell thruster among trained soccer players. Twenty male-trained soccer players aged 17 to 20 (18.99 ± 0.75) were recruited for this study. An experimental crossover study design was conducted with participants undergoing a general or specific warm-up protocol before 1RM testing. The results indicated that the specific warm-up protocol (51.25 ± 8.68 kg) significantly enhanced 1RM barbell thruster performance compared to the general warm-up (42 ± 6.42 kg), demonstrating superior strength outcomes and improved neuromuscular activation (p = 0.04 < 0.05). On top of that, there are also significant differences in the time efficiency of the warm-up protocol (p = 0.00 < 0.05), which favors a specific warm-up protocol (106.85 ± 8.76 sec). These findings highlight the importance of tailored warm-up strategies in enhancing strength performance and time optimization. The implications of this research are vital for coaches and practitioners in developing effective training regimens for soccer players, contributing to the broader body of knowledge in sports science. Future research should explore the long-term effects of specific warm-up protocols across different athletic populations and examine the underlying physiological mechanisms driving performance improvements.